2020
DOI: 10.1101/2020.01.08.899278
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A silent disco: Differential effects of beat-based and pattern-based temporal expectations on persistent entrainment of low-frequency neural oscillations

Abstract: Psychology, Vrije Universiteit Amsterdam (h.a.slagter@vu.nl). AbstractTemporal expectations (e.g., predicting "when") facilitate sensory processing, and are suggested to rely on entrainment of low frequency neural oscillations to regular rhythmic input.However, temporal expectations can be formed not only in response to a regular beat, such as in music ("beat-based" expectations), but also based on a predictable pattern of temporal intervals of different durations ("memory-based" expectations). Here, we examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 150 publications
0
11
1
Order By: Relevance
“…In Experiment 1, sustained MEG oscillations were maximal at parietal sensors and had a clearly different scalp topography and source configuration from typical auditory responses (cf. [ 46 ] for a similar shift towards parietal sensors after rhythmic stimulation). In Experiment 2, individual tACS phase lags leading to highest word report accuracy after tACS offset were unrelated to those measured during tACS.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In Experiment 1, sustained MEG oscillations were maximal at parietal sensors and had a clearly different scalp topography and source configuration from typical auditory responses (cf. [ 46 ] for a similar shift towards parietal sensors after rhythmic stimulation). In Experiment 2, individual tACS phase lags leading to highest word report accuracy after tACS offset were unrelated to those measured during tACS.…”
Section: Discussionmentioning
confidence: 81%
“…Both perception and electrophysiological signals have been shown to briefly oscillate after a rhythmic sequence of simple visual [40][41][42] or auditory [43][44][45] stimuli, such as flashes or pure tones. A recent study showed that such a sustained rhythmic response occurs when preceded by a stimulus evoking the perception of a regular beat, but not when participants merely expect the occurrence of a rhythmic event [46]. Although neural entrainment is widely explored in speech research [1,2], we are only aware of 1 study reporting sustained oscillatory effects produced by human speech: Kösem and colleagues [17] showed that, immediately after a change in speech rate, oscillatory MEG responses can still be measured at a frequency corresponding to the preceding speech (summarized in [15]).…”
Section: Endogenous Neural Oscillations Entrained By Rhythmic Sensory and Electrical Stimulationmentioning
confidence: 99%
“…Both perception and electrophysiological signals have been shown to briefly oscillate after a rhythmic sequence of simple visual [4042] or auditory [4345] stimuli, such as flashes or pure tones. A recent study showed that such a sustained rhythmic response occurs when preceded by a stimulus evoking the perception of a regular beat, but not when participants merely expect the occurrence of a rhythmic event [46]. Although neural entrainment is widely explored in speech research [1,2], we are only aware of one study reporting sustained oscillatory effects produced by human speech: Kösem et al [17] showed that, immediately after a change in speech rate, oscillatory MEG responses can still be measured at a frequency corresponding to the preceding speech (summarized in [15]).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, while some consider metre to be a property of rhythm that is emergent from the presence of a beat in a dynamical systems perspective [25], others consider the hierarchical perception of metre as distinct from beat perception, and more related to language processing [6]. Thus, the precise relationship and interdependence of processing of rhythmic patterns, a beat and metre remains a topic for future research [26,27]. It is also often not clear which type of structure elicits rhythmic behaviour.…”
Section: Components Of Rhythmic Abilitiesmentioning
confidence: 99%
“…Meter Musical notation relationship and interdependence of processing of rhythmic patterns, a beat, and meter remains a topic for future research [26,27]. It is also often not clear which type of structure elicits rhythmic behavior.…”
Section: Beatmentioning
confidence: 99%